Two phospholipase A2 inhibitors from the plasma of Cerrophidion (Bothrops) godmani which selectively inhibit two different group-II phospholipase A2 myotoxins from its own venom: isolation, molecular cloning and biological properties - Lizano González, Sergio (2000)
Myotoxic phospholipases A2 (PLA2s; group II) account for most of the muscle-tissue damage that results from envenomation by viperid snakes. In the venom of the Godman's viper (Cerrophidion godmani, formerly Bothrops godmani), an enzymically active PLA2 (myotoxin I) and an inactive, Lys-49 variant (myotoxin II) induce extensive muscle damage and oedema. In this study, two distinct myotoxin inhibitor proteins of C. godmani, CgMIP-I and CgMIP-II, were purified directly from blood plasma by selective binding to affinity columns containing either myotoxin I or myotoxin II, respectively. Both proteins are glycosylated, acidic (pI = 4) and composed of 20-25-kDa subunits that form oligomers of 110 kDa (CgMIP-I) or 180 kDa (CgMIP-II). In inhibition studies, CgMIP-I specifically neutralized the PLA2 and the myotoxic, oedema-forming and cytolytic activities of myotoxins I, whereas CgMIP-II selectively inhibited the toxic properties of myotoxin II. N-terminal amino acid sequence analysis and sequencing of cDNAs encoding the two inhibitors revealed that CgMIP-I is similar to γ-type inhibitors, which share a pattern of cysteine residues present in the Ly-6 superfamily of proteins, whereas CgMIP-II shares sequence identity with α-type inhibitors that contain carbohydrate-recognition-like domains, also found in C-type lectins and mammalian PLA2 receptors. N-terminal sequencing of myotoxin I revealed a different primary structure from myotoxin II [De Sousa, Morhy, Arni, Ward, Díaz and Gutiérrez (1998) Biochim. Biophys. Acta 1384, 204-208], which provides insight into the nature of such pharmacological specificity.